Characterization of the functional and transcriptomic effects of pro-inflammatory cytokines on human EndoC-βH5 beta cells - Frørup, Caroline; Gerwig, Rebekka; Svane, Cecilie Amalie Søndergaard; Mendes Lopes de Melo, Joana; Henriksen, Kristine; Fløyel, Tina; Pociot, Flemming; Kaur, Simranjeet; Størling, Joachim (Frontiers in Endocrinology, 2023)
Objective EndoC-βH5 is a newly established human beta-cell model which may be superior to previous model systems. Exposure of beta cells to pro-inflammatory cytokines is widely used when studying immune-mediated beta-cell failure in type 1 diabetes. We therefore performed an in-depth characterization of the effects of cytokines on EndoC-βH5 cells. Methods The sensitivity profile of EndoC-βH5 cells to the toxic effects of interleukin-1β (IL-1β), interferon γ (IFNγ) and tumor necrosis factor-α (TNFα) was examined in titration and time-course experiments. Cell death was evaluated by caspase-3/7 activity, cytotoxicity, viability, TUNEL assay and immunoblotting. Activation of signaling pathways and major histocompatibility complex (MHC)-I expression were examined by immunoblotting, immunofluorescence, and real-time quantitative PCR (qPCR). Insulin and chemokine secretion were measured by ELISA and Meso Scale Discovery multiplexing electrochemiluminescence, respectively. Mitochondrial function was evaluated by extracellular flux technology. Global gene expression was characterized by stranded RNA sequencing. Results Cytokines increased caspase-3/7 activity and cytotoxicity in EndoC-βH5 cells in a time- and dose-dependent manner. The proapoptotic effect of cytokines was primarily driven by IFNγ signal transduction. Cytokine exposure induced MHC-I expression and chemokine production and secretion. Further, cytokines caused impaired mitochondrial function and diminished glucose-stimulated insulin secretion. Finally, we report significant changes to the EndoC-βH5 transcriptome including upregulation of the human leukocyte antigen (HLA) genes, endoplasmic reticulum stress markers, and non-coding RNAs, in response to cytokines. Among the differentially expressed genes were several type 1 diabetes risk genes. Conclusions Our study provides detailed insight into the functional and transcriptomic effects of cytokines on EndoC-βH5 cells. This information should be useful for future studies using this novel beta-cell model.